FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TONSILLITIS PADA ANAK USIA SEKOLAH DI POLI KLINIK RSUD LABUANG BAJI MAKASSAR - Rini Mustamin (Stikes Graha Edukasi Makassar, 2018)
Objective: To find out factors related to the incidence of tonsillitis in school-age children in Poli Klinik RSUD Labuang Baji Makassar. Method: This study used descriptive analytic design, with cross sectional study approach where the objective was to know factors related to the incidence of tonsillitis in school-aged children in Poli Klinik RSUD Labuang Baji Makassar. As for the sample size in this study 49 respondents in accordance with inclusion criteria. The data were collected by means of questionnaire distribution, where to see the relationship of mother knowledge, lifestyle, and environment with the incidence of tonsillitis. In this study using chi-square test. at significance level ? = 0.05. Results: Based on the results of the study, there was a correlation between maternal knowledge and the incidence of tonsillitis (p = 0.041), lifestyle relationship with tonsillitis (p = 0,008), and environmental relationship with tonsillitis (p = 0,030). Discussion: Tonsillitis is a peradagang on light tonsils. Inflammation of the tonsils in children almost always involves people around them so that infection on the pharynx usually also concerns the tonsils so that it is called as tonsilofaringitis. Conclusion: The conclusion in this research is there is relationship of mother knowledge, lifestyle and environment with the incidence of tonsilitis. Suggestion: Suggestion The results of this study is expected to the mother in order to increase the level of knowledge in overcoming the disorders of tonsillitis in school-age children and can be useful as a reference source for improving the completeness of data sufferers tonsilitis